Encyclopedia of electrical engineering - Jaiswal, Manoj (New Delhi, India : Anmol Publications, 2006)
The Encyclopaedia of Electrical Engineering covers all the aspects of Electrical Engineering and its role in society.
Keywords: ELECTRICAL ENGINEERING -- ENCYCLOPAEDIA